Topology-optimized lattice structures with simultaneously high stiffness and light weight fabricated by selective laser melting: Design, manufacturing and characterization. (August 2020) - Zhang, L.; Song, B.; Fu, J.J.; Wei, S.S.; Yang, L.; Yan, C.Z.; Li, H.; Gao, L.; Shi, Y.S.
Highlights: Lattice structures were designed by topology optimization method. The deformation characterizations were observed by experiments. The stress distribution was analyzed by finite element method. The cell number influences the fracture mode. The energy absorption capability depends on the deformation process. Abstract: In this study, the level set-based topology optimization method was adopted to design novel lattice structures. The Ti-6Al-4V topology-optimized lattice structures with 30 % volume of solid materials were successfully fabricated by selective laser melting (SLM). The study on mechanical properties and energy absorption capability of the topology-optimized structures was also conducted through the quasi-static compressive testing. Results showed that as the unit cell number of lattice structures increases, the structural failure mechanism changes from the layer-by-layer fracture to the 45° inclined fracture. Topology-optimized lattice structures have a better relative elastic modulus of 0.037 than that of the majority of reported lattice structures, and the as-designed lattice structures possess relatively high energy absorption efficiency of 67.9 % at 0.15 strain. The findings illustrated that the proposed topology optimization method combined with SLM processing is an effective way to obtain novel lattice structures with high load-bearing and energy absorption capacities.